New chirp-free and chirped form optical solitons to the non-linear Schrodinger equation - Zafar, Asim; Raheel, M.; Rezazadeh, Hadi; İnç, Mustafa; Akinlar, Mehmet Ali (Springer, 2021)
We are concerned with new form optical solitons to the non-linear Schrodinger equation (NLSE) by generalized anti-cubic non-linearity. Some new optical solitons containing dark, singular and periodic solitons in chirp-free and chirped form are constructed via modified extended tanh expansion method. These results are very useful in the field of optics. The obtained results are verified and also explain by drawing different graphs. Parametric conditions for the chirp-free and chirped shape soliton solutions are also mentioned. Computational results indicate the efficiency of the aforesaid analytical expansion scheme.
Keywords: Generalized nonlinearity; Optical solitons; Modified extended tanh expansion scheme